Management and Ethics - Estrada García, † Ricardo A.; Monroy Alvarado, † Germán S.; Cortés Cortés, Manuel A. (Administración y Organizaciones, 2025)
In the face of the accelerated changes that our societies have undergone in recent decades —both in scientific and technological realms, as well as in social, economic, and cultural spheres— it can be observed that certain fundamental and indispensable aspects for development remain forgotten, at individual, social, and humanity -wide levels. Within this context, concepts such as ethics seem to be marginalized when considering, for example, the high levels of corruption everywhere. This paper explores the importance of ethical issues in professional and academic activities related to management, which lean on a chance to improve efficiency and efficacy as well as individual, organizational, and social development.